Pornograpfi Dalam Perspektif Hukum Islam dan Undang-Undang 44 Tahun 2008 (Suatu kejadian yuridis Normatif) - Ruslan Abdul Ghani (Al-Risalah, 2010)
This article juxtaposes islamic legal views on pornograpy with positive law pronouncement on the same issue. It specifically explains the nature of MUI fatwa no. 287/ 2001 on pornography by which MUI recommended the state to pass the law againts pornography. it considers MUI's action as preventive measures to protect community pornography and its associented products.